AIP Conference Proceedings 2009
DOI: 10.1063/1.3179948
|View full text |Cite
|
Sign up to set email alerts
|

DEM Simulation of a Schulze Ring Shear Tester

Abstract: The Schulze ring shear tester allows measurement of yield loci for bulk granular solids and of the friction between the solids and the container wall material. These measurements are required inputs in a systematic design method for hoppers. The measurements are subject to test-to-test variations caused by the combined effects of several factors, such as cell filling technique, sampling technique, particle size and shape distribution of the loaded sample and cell size relative to the particle size. One difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…It is known from quantum mechanics that the E1 response of nuclei is [9,13] S whereD is the dipole operator, E 0 is the energy of the ground state |0 , while the energies E n correspond to the excited states |n , eigenstates of the Hamiltonian of the system. The corresponding strength function in the semiclassical framework can be obtained by the Fourier transformation of the perturbation observable…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from quantum mechanics that the E1 response of nuclei is [9,13] S whereD is the dipole operator, E 0 is the energy of the ground state |0 , while the energies E n correspond to the excited states |n , eigenstates of the Hamiltonian of the system. The corresponding strength function in the semiclassical framework can be obtained by the Fourier transformation of the perturbation observable…”
Section: Resultsmentioning
confidence: 99%
“…In refs. [8,9], a microscopic transport model based on the Landau-Vlasov kinetic equation was used to systematically study the correlation between the PDR peak position and the mass number of the nucleus considered, and the correlation between the Energy-Weighted Sum Rule (EWSR) attributed to the PDR mode and the neutron skin thickness. The role of the isovector sector of the nuclear effective interaction was also explored, by considering three different parametrizations of the symmetry energy, but momentum dependent effects were neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing particle rotation can also increase the internal friction angle . The effect of particle stiffness was shown to be limited in the high stiffness range while it was more significant in the low stiffness range, and cohesive forces between particles caused an increase in the peak shear stress while it had no effect on the steady‐state stress . The particle Poisson's ratio, coefficient of restitution, and particle‐wall friction coefficient were found to have insignificant effects on shear test outcomes .…”
Section: Introductionmentioning
confidence: 96%
“…The particle‐particle friction coefficient, which may be difficult to measure (for fine powders in particular), has been calibrated by fitting numerical simulation results to experimental measurements of a shear tester . A sensitivity analysis using DEM simulations of shear tests has shown that particle‐particle friction coefficients (sliding and rolling) dominate shear test outcomes . Particle shape also has a significant effect: larger angles of internal friction were obtained for angular particles and elongated particles with moderate particle aspect ratios in the range from one to two as a result of the interlocking of particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation